Association of mitochondrial displacement loop polymorphisms with diarrhea‐predominant irritable bowel syndrome: A preliminary study. Issue 5 (6th May 2018) - Liu, Zi Yu; Gua, Xia Xu; Zhang, Rong Gui; Wang, Xiao Xiao; Ai, Jie; Wang, Wei Feng; Yang, Yun Sheng
Abstract : OBJECTIVES: To investigate whether single nucleotide polymorphisms (SNPs) in the mitochondrial displacement loop (D‐loop) were associated with irritable bowel syndrome (IBS). METHODS: Altogether 40 participants were recruited and classified into three groups, including 20 that fulfilled the Rome III criteria for diarrhea‐predominant IBS (IBS‐D), 10 with constipation‐predominant IBS (IBS‐C), and 10 healthy volunteers (controls). DNA was extracted from biopsy specimens of the colon obtained during routine colonoscopies. The mitochondrial D‐loop was sequenced and variants were identified in comparison with the reference sequence from GenBank. We searched GenBank and MITOMAP to determine whether a variant could be considered an SNP. RESULTS: No significant differences in sex, age and body mass index were found among the three groups. The average numbers of SNPs in the IBS‐D, IBS‐C and control groups were 12.2 ± 2.7, 9.8 ± 1.8 and 9.9 ± 2.1, respectively. The frequency of SNPs was significantly higher in the IBS‐D group than in the IBS‐C group and controls ( P < 0.05). No significant difference was found between the latter two groups. Each SNP was compared among the three groups and the frequency of 199C was found to be significantly higher in the control group than in the IBS‐D group ( P = 0.03), but no significant difference in its frequency was found between the IBS‐C group and controls. CONCLUSIONS: Patients with IBS‐D have a higher incidence of SNPs in the mitochondrial D‐loop than controls. The genotype 199C may be associated with a lower risk of IBS‐D.